ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN BUAH IMPOR DI PASAR JOHAR KOTA SEMARANG (Studi Kasus Buah Apel Fuji dan Jeruk Mandarin) - Fery Alfauzan; Endah Subekti; Shofia Nur Awami (Universitas Wahid Hasyim, 2015)
Indonesian agricultural products can be used as the leading commodity in the global competition, horticultural products especially such as fruits. The objectives of this resarch to know the characteristics of the consumer to purchase and consume the imported fruits, analyze the factors that affecting consumer behavior toward the demand of Fuji Apples and Mandarin Oranges in Johar Market. The sample area of research selected by purposive methods. The sample respondents of research with accidental sampling. The area of research in Johar Market Semarang City, which provide product of Fuji Apples and Mandarin Oranges. The total sample of respondents were taken as many as 88 respondents, which were consisted of 44 respondents Fuji Apples and 44 respondents Mandarin Oranges. Consumer of Fuji Apples and Mandarin Oranges were aged 31 until 40 years old. The average income of the consumers of the Mandarin Oranges was Rp.2.193.182 and the average income of the consumers of Fuji Apples was Rp.2.531.818. The status of their profession is as a housewife with a high school education level. They have number of family members from 3 - 4 people. The factors that affecting the demand of Fuji Apples are age, income, price. The factors that affecting demand of Mandarin Oranges are income and price. Keywords: Consumer Behavior, Fruit Import, Fuji Apples, Mandarin Oranges Purchasing Decisions.